The Role of Qur’an-Hadith Teachers in Overcoming Memorization Difficulties among Grade IX Students at MTs Negeri Kota Sorong - Rahma, Wa (Indonesian Journal of Islamic Educational Review, 2025)
Memorizing the Qur’an and Hadith is a fundamental element of Islamic education, serving as a spiritual discipline and an academic requirement. In formal Islamic secondary schools (madrasah tsanawiyah), students are expected to achieve specific memorization targets within the national curriculum. However, many face significant obstacles that impede this process, ranging from limited reading fluency and low intrinsic motivation to insufficient parental involvement. This study explores the multifaceted role of Qur’an-Hadith teachers in overcoming such challenges among Grade IX students at MTs Negeri Kota Sorong, identifies the difficulties they encounter, and analyzes the strategies they employ. Using a qualitative approach grounded in Islamic pedagogy and supported by modern educational theory, data were collected through eight observation sessions, in-depth interviews with three Qur’an-Hadith teachers, twelve students, and four parents, as well as the analysis of lesson plans, assessment records, and memorization logs. The data were analyzed using Miles, Huberman, and Saldana’s interactive model, with validity ensured through triangulation of sources and methods. The findings reveal that teachers function as motivators by offering praise, grades, and rewards; as facilitators by employing talaqqi and sima’i methods alongside audiovisual aids and adaptive approaches for varying abilities; as mentors by providing individual guidance outside class hours; and as evaluators through regular oral tests and recitation submissions. The challenges they face include heterogeneous reading skills, fluctuating motivation, and weak parental engagement. Strategies to address these involve collective repetition, contextualization of verses, memorization competitions, and sustained communication with parents. This study offers a conceptual framework that links classroom practices with broader educational theory, emphasizing the necessity of a synergistic approach between teachers, students, and parents for effective memorization. Its implications extend to curriculum design, teacher professional development, and community involvement in Qur’an and Hadith memorization initiatives.